Phonological analysis of syllabic changes of Arabic loan verbs - Muhaimin Syaqiq Mawaridi,; Abdul Azim Mohamad Isa,; Lutfi Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The original form of a language is often changed when the language is borrowed into the target language. In Malay, one of the changes that can be observed is the reduction of syllable segments. The change results from integrating and adapting the source language to the target language for native-like adaptation. Therefore, this study investigates the reduction of syllable segments and phonological changes of syllable segments in Arabic loan verbs. The reduction of syllable segments refers to a segmental reduction in the first, second or third syllable. The phonological change of the syllable segment refers to the sound change that occurs when the syllable segment is reduced. This study uses Arabic loan verbs in Kamus Dewan Perdana as research data. The collected data was transcribed and 30 Arabic loanwords were found to have syllable segment reduction. The data is then analysed using the theory of sound change to determine the phonological changes that occur in the syllable segments in the Arabic loanwords. The study results show that there are 3 types of segmental reduction located in the first syllable, 26 verbs in the second syllable and 3 verbs in the third syllable. In addition, the study's results also show that phonological changes for syllable segments in Arabic loanwords occur through vowel adaptation, neutralization and scramble. These changes generally take the form of vowel adjustments that shorten the vowel sound of the original Arabic spelling, which accounts for most of the sound changes in syllable segment reduction.